ESTIMASI CADANGAN KARBON DI ATAS PERMUKAAN PADA HUTAN DESA BUNTOI KABUPATEN PULANG PISAU KALIMANTAN TENGAH (Above-Ground Carbon Pool Estimation at the Buntoi Village, Pulang Pisau District, Central Kalimantan Province): Yusuf Aguswan - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2015)
ABSTRACTVillage forest program is one of the breakthroughs of the Ministry of Forestry for community-based forest management. In order to manage the village forest, needing the data and information about the biomassa at the site. The research was aimed to estimate the above-ground carbon pool at the Buntoi Village Forest that located at the protection forest in the form of deep peat areas. This site is administratively located at the Pulang Pisau District, Central Kalimantan Province. Research result showed that above-ground carbon pool at the peat-swamp scrub of Buntoi Village Forest is predictively namely 16.510 ton, whereas above-ground carbon pool at peat-swamp secondary forest of Buntoi Village Forest is predictively namely 176.059 ton. These data are lower than Central Kalimantan REL standard, with the result the Buntoi Village Forest is suitable for carbon trade purpose at the future.Keywords: Buntoi, carbon pool, peat-swamp areas, village forest